Rapid separation and identification of phosphatidylethanolamine molecular species - Jos F.H.M. Brouwers; Elisabeth A.A.M. Vernooij; Aloysius G.M. Tielens; Lambert M.G. van Golde (Journal of Lipid Research, 1999)
A novel high performance liquid chromatography method is presented for the separation and identification of intact molecular species of phosphatidylethanolamine (PE). After isocratic separation, detection of species can be achieved by measurement of UV absorbance as well as by the quantitative method of light scattering detection. A mathematical relationship exists between i) the relative retention time of a PE molecular species and ii) the number of carbon atoms and double bonds in the aliphatic groups of the species. This relationship can aid in the identification of the species. Furthermore, the absence of non-volatile components in the solvent allows the use of electrospray mass spectrometry to identify the eluting components and to establish the position of the individual radyl groups at the glycerol backbone. Using this method, samples of bovine heart PE (rich in plasmalogens) and rat liver PE (rich in diacyl species) have been analyzed.—Brouwers, J. F. H. M., E. A. A. M. Vernooij, A. G. M. Tielens, and L. M. G. van Golde. Rapid separation and identification of phosphatidylethanolamine molecular species. J. Lipid Res. 1999. 40: 164–169.